Optical frequency ratio of a 171Yb+ single-ion clock and a 87Sr lattice clock. (7th January 2021) - Dörscher, S; Huntemann, N; Schwarz, R; Lange, R; Benkler, E; Lipphardt, B; Sterr, U; Peik, E; Lisdat, C
Abstract: We report direct measurements of the frequency ratio of the 642 THz S 1 / 2 2 ( F = 0 ) – F 7 / 2 2 ( F = 3 ) electric octupole transition in 171 Yb + and the 429 THz S 0 1 – P 0 3 transition in 87 Sr. A series of 107 measurements has been performed at the Physikalisch-Technische Bundesanstalt between December 2012 and October 2019. Long-term variations of the ratio are larger than expected from the individual measurement uncertainties of few 10 −17 . The cause of these variations remains unknown. Even taking these into account, we find a fractional uncertainty of the frequency ratio of 2.5 × 10 −17, which improves upon previous knowledge by one order of magnitude. The average frequency ratio is ν Y b + / ν S r = 1.495 991 618 544 900 537 ( 38 ) . This represents one of the most accurate measurements between two different atomic species to date.